FROM THE WORLD RELIGION VIEW TO THE GEERTZIAN APPROACH IN INTERPRETING A CULTURE: An Excursion to Traditional Economic Ritual of Javanese in Langsih Cave - Taufiqurrohim, Taufiqurrohim (IAIN Ponorogo, 2019)
Abstract: Langsih cave offers the space for the ritual which fulfills the requirement of Javanese tradition called Pesugihan defining as a supernatural practice and belief in getting rich quick through mysticism and the people should do such a ritual in a sacred place with the particular rule. Through the symbol and ritual experiences, there would find how the people chronologically believe in the sacred ritual that would conducive to the wealth of the ritual. Thus, this paper firstly tries to point out the role of Langsih cave as the site of traditional economic ritual for Javanese culture. The next discussion is examining the existence of pesugihan as on how the worldview representation to the ritual. The last is arguing the optional perspective based on Geertzian approach, which it offers interpretative theory of the culture at the semiotic experience due to its explication â€œconstruing social expressions on their surface enigmaticalâ€ but it still needs an explanation. The paper shows that the traditional economic ritual is surely a practice transcending from the ancestor unconsciously and the culture seems to be blurred because the role of the tough should be more rational, modernized or religious.Ø§Ù„Ù…Ù„Ø®Øµ: ÙŠØ³ÙˆØ±ØºØ§Ø±Langsih Â Ø§Ù„ÙØ±Ø§Øº Ù„Ø·Ù‚ÙˆØ³ Ø§Ù„Ø°ÙŠ ÙŠØ£Ø¯ÙŠ Ø¥Ù„ÙŠ Ø´Ø±ÙˆØ· ØªÙ‚Ù„ÙŠØ¯ Ø§Ù„Ø¬Ø§ÙˆÙŠØ© Ø§Ù„ØªÙŠ ØªØ³Ù…ÙŠpesugihan Â . Ø§Ù„Ù…Ù‚ØµØ¯ Ù…Ù† Â pesugihan ÙŠØ¹Ù†ÙŠ Ù…Ù…Ø§Ø±Ø³Ø© Ø§Ù„Ø®Ø§Ø±Ù‚ Ùˆ Ø§Ù„ØªØµØ¯ÙŠÙ‚ Ù„ØªÙƒÙˆÙ† ØºÙ†ÙŠØ§ Ø¨Ø³Ø±Ø¹Ø© Ø¨ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØµÙˆÙ, ÙˆÙˆØ¬Ø¨ Ù„ÙƒÙ„ Ù†ÙØ± Ø§Ù„Ø·Ø§Ø¹Ø© Ø¹Ù„ÙŠ Ø§Ù„Ø·Ù‚ÙˆØ³ ÙÙŠ Ø£ÙŠ Ù…ÙƒØ§Ù† Ùˆ Ø¨Ù‚ÙˆØ§Ø¹Ø¯ Ù…Ø¹ÙŠÙ†. Ø¨ØªÙÙ‡ÙŠÙ… Ø§Ù„Ø±Ù…Ø² ÙˆØªØ¬Ø±Ø¨Ø© Ø§Ù„Ø·Ù‚ÙˆØ³ Ø³ÙŠÙƒÙˆÙ† Ù‡Ù†Ø§Ùƒ Ø·Ø±ÙŠÙ‚Ø© Ù„Ù„Ù†Ø§Ø³ Ù„ÙÙ‡Ù… Ø¨Ø´ÙƒÙ„ Ø·Ø¨ÙŠØ¹ÙŠ Ø¹Ù† Ø§Ù„Ø·Ù‚ÙˆØ³ Ø§Ù„Ù…Ù‚Ø¯Ø³Ø© Ø§Ù„ØªÙŠ ØªÙØ¶ÙŠ Ø¥Ù„Ù‰ Ø§Ù„Ø«Ø±ÙˆØ© Ø§Ù„Ø·Ù‚ÙˆØ³ÙŠØ©. ÙÙÙŠ Ø£ÙˆÙ„ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø³ØªØ¸Ù‡Ø± Ø¥Ù„ÙŠ Ø¯ÙˆØ± ØºØ§Ø±Langsih Â Â ÙƒÙ…ÙƒØ§Ù† Ø§Ù„Ø·Ù‚ÙˆØ³ Ø§Ù„Ø¥Ù‚ØªØµØ§Ø¯ Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠ Ù„Ø«Ù‚Ø§ÙØ© Ø§Ù„Ø¬Ø§ÙˆÙŠØ©. ÙˆÙ…Ù†Ø§Ù‚Ø´Ø© Ø¨Ø¹Ø¯Ù‡Ø§ ÙŠØ¹Ù†ÙŠ Ø§Ù„Ø¨ØØ« Ø¹Ù† Ø§Ù„ØªÙ…Ø«ÙŠÙ„ Ø§Ù„Ù†Ø¸Ø±Ø© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ø¹Ù„ÙŠ ØªÙ„Ùƒ Ø§Ù„Ø´Ø¹ÙŠØ±Ø©. ÙˆØ§Ù„Ø£Ø®Ø± ÙŠØ¹Ù†ÙŠ Ø§Ù„ØªÙ†Ø§Ø²Ø¹ Ø¹Ù† Ù…Ù†Ø¸ÙˆØ± Ø§Ù„Ø¥Ø®ØªÙŠØ§Ø±ÙŠ Ø¨Ù†Ø§Ø¡ Ø¹Ù„ÙŠ Ù†Ù‡Ø¬Geertzian Â , Ø§Ù„Ø°ÙŠ ÙŠØ¹Ø±Ø¶ Ø¹Ù† Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ø§Ù„ØªÙØ³ÙŠØ±ÙŠØ© Ø¨ØªØ¬Ø±Ø¨Ø© Ø´Ø¨Ù‡ Ù„Ø£Ù† ØªÙØ³ÙŠØ±